PENGGUNAAN METODE GROUP INVESTIGATION BERBASIS KONTEKSTUAL PADA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI IPA-2 DI SMAN 3 MATARAM - Abdul Khalik (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The aim of this research is to know how the group investigation method that contextual basically can increase the students’ activities and the students’ result in learning of the XI science 2 at SMAN 3 Mataram in 2013-2014 academic year. Based on the research it can be said that this method can increase them by seeing the result of students' activities in the first cycle gets 2,42 become 3,13 in the second cycle and the teachers’ activities from 3,13 in the first cycle become 3.5 in the second cycle. The students’ result in learning from an average 53,33 in the first cycle become 73,71 in the second cycle